Dari Doktrin ke Emansipasi: Rekonstruksi Teologi Islam sebagai Paradigma Konseling Profetik-Transformatif - Libya Rizki Adya Nova; Anisa Nurcahya; Intana Azkia Afkareza; Amrina Rosyada; Ali Hasan Siswanto (Indo Publishing, 2026)
This article departs from a fundamental crisis in contemporary Islamic theology, characterized by a disconnect between normative-doctrinal constructs and transformative social practice. Although the discourses of Modern Theology, Liberation Theology, and Transformative Islamic Theology have developed, significant gaps remain in integrating the theological dimension with operational, practical approaches, particularly in the context of Islamic values-based social counseling. The primary research gap lies in the absence of a conceptual formulation that positions amar ma'ruf nahi munkar as a dialogical, emancipatory, and transformative counseling paradigm, rather than merely a prescriptive normative instrument.This article employs an integrative theoretical approach that combines the epistemology of revelation with critical social theory and prophetic ethics. The research method employed is qualitative-conceptual, using a literature review with critical and hermeneutic analysis. The article's primary argument is that reconstructing Islamic theology toward a prophetic-transformative counseling paradigm enables the transformation of the concept of amar ma'ruf nahi munkar into a social therapeutic process oriented toward critical awareness, empowerment, and structural change.This article's scholarly contribution lies in the development of a new paradigm of